Parameters affecting fluctuation in traffic stream on urban roads. (May 2019) - Al-Bahr, T. M.; Puan, O. C.; Hassan, S. A.; Idham, M. K.; Ismail, C. R.
Abstract: Moving Observer Method (MOM) is one of traffic data collection techniques that being used to collect the traffic flow at the urban roads. However, this technique is sensitive to the normal fluctuation of the traffic flow. Road length, intersection density, and driveway density are three main parameters contributed to the fluctuation of traffic flow in urban roads. This paper attempts to determine how much range of these parameters are affecting the fluctuation of the traffic flow. By using MOM technique, twenty urban roads in Johor Bahru city are selected randomly to analyse how these parameters contribute to this fluctuation of the traffic flow. Regression analysis is performed to identify the range of the effect of these parameters on the accessibility and fluctuation rate of traffic flow in urban roads. It is found that driveway density is significantly affecting the fluctuation of traffic flow followed by road length.